مستوى التفكير التأملي واللياقة العقلية وعلاقتهما بالتحصيل الدراسي لدى طلبة قسم العلوم / كلية التربية الاساسية في مادة اللافقاريات. - رانيا محمد جسام; سارة حاجم عبد ال&#1589 (Journal of Babylon Center for Humanities Studies, 2026)
The present study aims to identify the level of reflective thinking and mental fitness, and their relationship to academic achievement among students of the Department of Science / College of Basic Education in the subject of Invertebrates. The research sample consisted of (55) male and female students from the Department of Science / Life Sciences Branch at the College of Basic Education, Wasit University, for the academic year (2023–2024). The two researchers constructed the scale items, whereby the Reflective Thinking Scale consisted of (20) items, while the Mental Fitness Scale consisted of (25) items, each with five response alternatives. The psychometric properties of both instruments were verified to ensure their validity and reliability for application. The researchers employed the descriptive method to obtain the data required for the study. After conducting statistical analyses using the Statistical Package for the Social Sciences (SPSS), the study reached the following results: -Students demonstrated a moderate level of reflective thinking. -Students possessed a moderate level of mental fitness. -Students achieved a good level of academic achievement. -There was a moderate positive correlation between reflective thinking and students’ achievement, which was statistically significant. -There was a moderate positive correlation between mental fitness and students’ achievement, which was statistically significant. In light of these findings, the researchers recommend that educational institutions place greater emphasis on developing students’ reflective thinking and mental fitness in order to enhance the teaching and learning process. They also recommend organizing training courses for instructors in educational institutions to raise awareness of different thinking styles, including reflective thinking, and how to apply its skills in teaching methods and various educational activities. Furthermore, the researchers suggest conducting additional studies to evaluate levels of mental fitness and reflective thinking among students at different educational stages, as well as to identify the causes and prevalence of difficulties related to learning reflective thinking within our society.